'Codeine crazy:' a content analysis of prescription drug references in popular music. (14th September 2021) - Peteet, Bridgette; Roundtree, Christopher; Dixon, Shapree; Mosley, Cami; Miller-Roenigk, Brittany; White, Joseph; Bediako, Mindy; Hitch, Anthony; McCuistian, Caravella
ABSTRACT: Prescription drug misuse (PDM) is a national problem in the U.S., particularly effecting youth ages 16–25. Drug-related messages in music are one known predictor of substance use for this population. Research suggests that racial/ethnic minority youth are less likely to engage in PDM; however, the prevalence of PDM references in rap music may better reflect emerging drug trends. This study examined changes in the frequency of references to PDM in rap lyrics in the top 25 songs in 2007 and 2017, using targets identified from a generated list of 235 slang terms for PDM. The lyrics for each song were obtained from Genius, a social media site with lyric annotations. Coders independently identified the target stanzas and a third member of the research team corroborated the selections. Results of the General Linear Model using a Negative Binomial distribution indicated that the number of songs referencing PDM was estimated to be 18.80 times higher in 2017 than in 2007. Implications for healthcare providers are provided.